Oil Palm Empty Fruit Bunch (OPEFB) handsheet production from optimized biodelignification of rhynchophorus ferrugineus microbiome’s enzymes - Mohd Aripin, Ashuvila; Abd Rashid, Amir Hamzah; Syarifah, Sharfina Mutia; Chan Chee Ming2, Chan Chee Ming2; Zainulabidin, Muhd Hafeez; Ishak, Nadiah; Adnan, Sharmiza; Seng Chye, Darren Lee; Mohd Kassim, Angzzas Sari (WARSE, 2020)
Oil palm plantation generates massive amount of oil palm empty fruit bunch (OPEFB) which source great amount of cellulose. However, wrapping this cellulose is an adhesive compound called lignin. Biodelignification process was applied to remove lignin in pulp and paper industry. Therefore, this study is focused on optimum conditions of delignification process using a combination of bacteria from Rhynchophorus ferrugineus on OPEFB. The composition of chemicals was characterized according to the TAPPI standard method and Kursher-Hoffner method. The Box-Behnken design (BBD) was used to determine the optimum conditions of delignification process based on lignin loss of OPEFB. The optimized fiber was investigated based on mechanical properties according to TAPPI standard methods. From BBD analysis, the finest conditions for delignification were recognized to be at 35 °C in 48 h incubation time with 5 mL of 1% glucose for predicted value 54.3% compared to experimental value 52% of lignin loss as revealed by confirmatory study. The highest result of chemical analysis was recognized at run 12 (1.15%), 10 (12.35%), 4 (48.99%) and 5 (1.28%) for extractive, lignin, cellulose and ash content respectively. The tensile, burst and tear were identified as 9.93 Nm/g, 0.98 kPa.m2/g and 2.57 mN.m2/g respectively for handsheet product at optimum conditions. In conclusion, the results obtained was indicated that the delignification process via bacteria combination from R. ferrugineus is a viable alternative pulping process for pulp and paper-based industry. The delignification process on OPEFB also provides a cleaner technology process and more sustainable development for the country.